PENGARUH IKLAN DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN MELALUI MINAT BELI SEBAGAI VARIABEL INTERVENING PADA UD ANUGERAH GRESIK - Ali Muhajir (J-MACC, 2024)
This research aims to determine the influence of advertising and price on purchasing interest, the influence of advertising and price on purchasing decisions, the influence of advertising on purchasing decisions through purchasing interest as an intervening variable and the influence of price on purchasing decisions through purchasing interest as an intervening variable at UD. Gresik Award. This research used the Purposive Sampling method with the Slovin formula so that 93 respondents could be obtained. The research was carried out with partial tests and path analysis using SPSS 25. The results of the coefficient of determination test based on the R Square value show that advertising, price and purchasing interest influence purchasing decisions by 41.4%. The results of the research show that advertising influences purchasing interest, price influences purchasing interest, advertising influences purchasing decisions, price influences purchasing decisions, advertising influences purchasing decisions through purchasing interest as an intervening variable and price influences purchasing decisions through purchasing interest as a variable. intervening.